Our Days of Gold: - Assunta Ruocco (Parse Journal)
This article examines the presentation of a personal photographic archive via the temporal and virtual space of social media through Our Days of Gold, an ongoing durational artwork constituted of a cluster of three interconnected Instagram accounts: @ourdaysofgold_film, @ourdaysofgold_digital and @ourdaysofgold. The project interweaves two separate temporalities: the social media accounts started in April 2017 to mark the first anniversary of my mother Cécile Barbiaux’s sudden death, drawing on an archive of analogue and digital photography recording an image-making collaboration that took place between 2002 and 2007. Staging a group of family and friends, the images oscillate between everyday activities and improvised performances within the confines of a familial territory of old farmhouses, orange groves and gardens in Sorrento, Italy. While the accounts are anonymous, the images, shared daily, are accompanied by captions that centre Cécile, even when she is not in the frame. Cécile is staged as the mysterious and alluring protagonist of her own unfolding story. Through its activation of Instagram’s languages, communities, specific structure and affordances, Our Days of Gold, or ODOG, creates a virtual space for a temporal paradox, where the past becomes contemporary by being stretched to excruciating slowness over the duration of the present, with one summer afternoon taking over nine months to share at the glacial pace of an image a day. Over its long duration, ODOG has become a palimpsest overwritten with followers’ contributions and interpretations. Through the anonymity and reticence that accompany the sharing of an intimate personal archive, ODOG provides a space for conversations and interactions, but also for silent, private accumulation of memories, familiarity and attachment.